Executives' Legal Records and the Deterrent Effect of Corporate Governance - Davidson, Robert H.; Dey, Aiyesha; Smith, Abbie (Contemporary Accounting Research, 2020)
ABSTRACT We study whether the effectiveness of corporate governance mechanisms varies depending on the characteristics of the executives subject to these mechanisms, namely their “psychological type,” as proxied by their history of legal infractions. In particular, we examine insider trading, where we can compare the trading behavior of different types of executives in the same firm. We find that “recordholder” executives, that is, those with prior legal infractions, earn significantly higher profits from purchases and sales than nonrecordholder executives. Furthermore, the profitability of both purchases and sales is significantly increasing in the severity of the infraction. Governance mechanisms, such as blackout policies, lower profits of executives with only traffic infractions; however, profits for executives with serious infractions appear insensitive to blackout policies. Insiders with serious infractions are also more likely to trade during blackout periods and before large information events and are more likely to report their trades to the SEC after the filing deadline. Collectively, our evidence suggests that while governance mechanisms can discipline executives with minor offenses, they appear largely ineffective for those with more serious infractions.